Exploring complex water stress–gross primary production relationships: Impact of climatic drivers, main effects, and interactive effects. (2nd May 2022) - Wang, Huan; Yan, Shijie; Ciais, Philippe; Wigneron, Jean‐Pierre; Liu, Laibao; Li, Yan; Fu, Zheng; Ma, Hongliang; Liang, Ze; Wei, Feili; Wang, Yueyao; Li, Shuangcheng
Abstract: The dominance of vapor pressure deficit (VPD) and soil water content (SWC) for plant water stress is still under debate. These two variables are strongly coupled and influenced by climatic drivers. The impacts of climatic drivers on the relationships between gross primary production (GPP) and water stress from VPD/SWC and the interaction between VPD and SWC are not fully understood. Here, applying statistical methods and extreme gradient boosting models—Shapley additive explanations framework to eddy‐covariance observations from the global FLUXNET2015 data set, we found that the VPD‐GPP relationship was strongly influenced by climatic interactions and that VPD was more important for plant water stress than SWC across most plant functional types when we removed the effect of main climatic drivers, e.g. air temperature, incoming shortwave radiation and wind speed. However, we found no evidence for a significant influence of elevated CO2 on stress alleviation, possibly because of the short duration of the records (approximately one decade). Additionally, the interactive effect between VPD and SWC differed from their individual effect. When SWC was high, the SHAP interaction value of SWC and VPD on GPP was decreased with increasing VPD, but when SWC was low, the trend was the opposite. Additionally, we revealed a threshold effect for VPD stress on GPP loss; above the threshold value, the stress on GPP was flattened off. Our results have important implications for independently identifying VPD and SWC limitations on plant productivity, which is meaningful for capturing the magnitude of ecosystem responses to water stress in dynamic global vegetation models. Abstract : The dominance of vapor pressure deficit (VPD) and soil water content (SWC) for plant water stress is still under debate. This study indicated that VPD was more important for plant water stress than SWC across most plant functional types when we removed the effect of main climatic drivers. However, we found no evidence for a significant influence of elevated CO2 on stress alleviation. Furthermore, applying the Shapley additive explanation method, we identified interactive patterns between VPD and SWC influencing gross primary production, which differed significantly from their individual effects.